Challenges of transarterial therapy for hepatocellular carcinoma in patients with chronic kidney disease. Issue 35 (August 2019) - Lin, Wei-Chen; Chang, Chen-Wang; Chang, Ching-Wei; Wang, Tsang-En; Chen, Ming-Jen; Wang, Horng-Yuan
Abstract : Abstract: Poor outcomes of hepatocellular carcinomas (HCC) in chronic kidney disease (CKD) patients are well described. Transarterial therapy is the standard treatment for HCC, following which regular contrast-enhanced imaging for residual disease is recommended. CKD is considered a relative contraindication for transarterial therapy owing to renal failure. This retrospective study investigated the outcomes of transarterial therapy in HCC patients with CKD. In total, 132 HCC patients who received transarterial therapy were enrolled, of whom 36 had CKD. Most CKD patients were elderly, with mean age of diagnosis of 69.7 ± 11.4 years. Hypertension (odds ratio [OR]; 5.06; 95% confidence interval [Cl]; 1.83–13.94), hepatitis C virus carrier rate (OR; 4.12, 95% CI; 1.13–14.99) and diabetes (OR; 3.62, 95% CI; 1.22–10.72) were significant predictors for CKD in HCC patients. Post therapy, the estimated glomerular filtration rate significantly decreased 13.7% from baseline in the CKD patients ( P  = .03). There were more post-therapy complications than in the non-CKD group, e.g. acute renal failure and sepsis ( P  < .01 vs P  < .01). Overall survival in the CKD group was significantly poor (10.9 ± 8.5 vs 23.5 ± 16.3 months, P  < .01). The lower survival of CKD patients was unrelated to treatment modality or less contrast-enhanced imaging follow-up. Further research on patient care and factors leading to poor outcomes for CKD is needed.